Swiping right: Sociosexuality, intentions to engage in infidelity, and infidelity experiences on Tinder. (15th October 2018) - Weiser, Dana A.; Niehuis, Sylvia; Flora, Jeanne; Punyanunt-Carter, Narissra M.; Arias, Vladimir S.; Hannah Baird, R.
Abstract: Tinder is a popular mobile dating app among young adults that may be used to facilitate meeting extradyadic partners. Participants who had used or were using Tinder (n = 550) indicated that most knew somebody who had used Tinder to meet extradyadic partners, and several participants reported that their own infidelity had been facilitated by Tinder. Participants were varied as to whether Tinder was an effective method for meeting extradyadic partners. Sociosexuality and intentions to engage in infidelity were associated with having used Tinder to engage in infidelity. Gender was not significantly associated with using Tinder to meet extradyadic partners when sociosexuality and intentions to engage in infidelity were also included in analyses. Highlights: A minority of participants reported infidelity facilitated by Tinder. Most knew individuals who had used to Tinder to engage in infidelity. Sociosexuality and intentions to engage in infidelity were associated with infidelity. Gender not associated with infidelity when sociosexuality and intentions included.